Stancu type Baskakov-Durrmeyer operators and approximation properties - Kilicman, Adem; Mursaleen, Mohammad Ayman; Al-Abied, Ahmed Ahmed Hussin Ali (MDPI AG, 2020)
In this article, we introduce Stancu type generalization of Baskakov–Durrmeyer operators by using inverse Pólya–Eggenberger distribution. We discuss some basic results and approximation properties. Moreover, we study the statistical convergence for these operators.